STRATEGIA CÂȘTIGĂTOARE A ARMATEI CAUCAZIENE PENTRU CUCERIREA CETĂȚII ERZURUM (FEBRUARIE 1916) - Bogdan MORAR (Intelligence și Cultura de Securitate)
In the summer of 1914, the two great military-political camps - the West and the Central Powers – unleashed the First World War. In early November 1914, the Ottoman Empire chose to side with the Central Powers. This led to the opening of a secondary front in the Caucasus where Turkish troops were to clash with Russian troops. The Battle of Sarikamis (22 December 1914-17 January 1915) ended in a great Russian victory, but both sides remained on the sidelines unprepared to strike the decisive blow. In 1915 the allies in Anatolia, notably Britain and France but without Russian participation, attempted to defeat Turkey by attacking the Dardanelles. The attack failed because the Ottomans concentrated significant troops near Constantinople. These troops were able to be withdrawn and redeployed after the Anglo-French withdrawal from the Turkish Straits. Intelligence warned Russia that the bulk of the Turkish troops were about to leave for the Caucasus. For this reason, the commander of the Caucasian Army, N.N. Yudenich was very anxious because he assumed that a resistance against them was very difficult. So he implemented a very bold plan. This article presents this plan and its results. To write the article I used written testimonies found in the RGVIA – Российский Государственный Военно-Исторический Архив (Russian State Historical-Military Archive) archive, including notes and positions sent by N.N. Yudenich to his superior, the viceroy of the Caucasus Nicholas Nikolaevich. The conclusions of the article highlight the winning strategy devised by N.N. Yudenich argues the author's personal opinion that this strategy (which included the conquest of Erzurum) was one of the greatest military victories of Tsarist Russia in the First World War.